1997
DOI: 10.1007/s004010050578
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase-like immunoreactivity in spheroids in Hallervorden-Spatz disease

Abstract: Iron accumulation in the basal ganglia and spheroid formation are pathological hallmarks of Hallervorden-Spatz disease (HS). Since an overaccumulation of iron (iron thesaurosis) that exceeds the binding capacity of ferritin could cause oxidative damage, we studied the possible role of oxidative stress in the pathogenesis of HS. The basal ganglia and spinal cord from patients with HS were investigated at autopsy, using histochemistry for iron and immunohistochemistry for Cu/Zn superoxide dismutase (SOD1), Mn su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Altered SOD expressions were identified also in child-onset neurodegenerative diseases such as Menkes' kinky hair disease [28], Hallervorden-Spatz disease [29], xeroderma pigmentosum and Cockayne syndrome [9]. In this analysis, immunoreactivity for Cu/ZnSOD was reduced in the external segment of globus pallidus and the cerebellar dentate nucleus in all DRPLA cases, regardless of the disease types.…”
Section: Discussionmentioning
confidence: 77%
“…Altered SOD expressions were identified also in child-onset neurodegenerative diseases such as Menkes' kinky hair disease [28], Hallervorden-Spatz disease [29], xeroderma pigmentosum and Cockayne syndrome [9]. In this analysis, immunoreactivity for Cu/ZnSOD was reduced in the external segment of globus pallidus and the cerebellar dentate nucleus in all DRPLA cases, regardless of the disease types.…”
Section: Discussionmentioning
confidence: 77%
“…By contrast, the deformed astrocytes and GFSBs showed weak Cu/Zn SOD‐immunoreactivity as compared to the Mn SOD‐immunoreactivity. In Hallervorden‐Spatz disease, an iron metabolic disorder analogous to ACP, it was reported that Cu/Zn SOD‐immunoreactivity was markedly increased, while the Mn SOD‐immunoreacticity was modestly increased in the characteristic neuroaxonal swelling ‘spheroid’[21]. This suggests that different mechanisms of antioxidative system may be involved in ACP and Hallervorden‐Spats disease, although both share the common pathophysiological background of iron‐mediated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The major histopathological hallmarks of NBIA 1 are axonal spheroids, 3,4,11,14 which have been shown to contain immunoreactive (IR) neurofilament (NF) proteins, 7,18,19 superoxide dismutase, 11 amyloid precursor protein (APP), 20 and ␣-synuclein (␣S). 18,19,21 In addition to spheroids, other characteristic lesions include glial cytoplasmic inclusions (GCIs), 18 Lewy body (LB)-like intraneuronal inclusions (NCIs), 7,13,18,19,22 and dystrophic neurites (DNs), 7,18,19 whereas in late onset NBIA 1, tau pathology has been demonstrated 14,22,23 consisting of both paired helical filaments and straight filaments without amyloid ␤-protein (A␤) deposition.…”
mentioning
confidence: 99%